'Ice Rushes', Data Shadows and Methylamphetamine Use in Rural Towns: Wastewater Analysis. Issue 3 (1st March 2018) - Prichard, Jeremy; Lai, Foon Yin; O'Brien, Jake; Bruno, Raimondo; Thai, Phong; Hall, Wayne; Kirkbride, Paul; Thomas, Kevin; Mueller, Jochen F
Abstract: Australia's world-class drug monitoring systems have difficulty gathering metrics in rural communities for reasons due to, among other things, the size of the country and problems with recruiting sufficient sample sizes. Some rural communities in data shadows (where few metrics on substance use exist) may benefit from wastewater analysis ('WWA') as a means of estimating per capita drug consumption. Wastewater analysis could be employed when debates rise about the consumption of particular drugs in certain communities. Other ways to use WWA are examined, including long-term monitoring of community drug consumption and intervention studies to test the effectiveness of health or law enforcement drug strategies. To explore the utility of WWA, this article references media coverage of methylamphetamine consumption in a small Tasmanian town, Smithton, and presents the results of the first Tasmanian WWA pilot study of methylamphetamine consumption, conducted in 2014–15.